Genetic polymorphism of scrA gene of Streptococcus mutans isolates is not associated with biofilm formation in severe early childhood caries - Yan Zhou; Lixia Yu; Ye Tao; Qinghui Zhi; Huancai Lin (BMC, 2017)
Abstract Background To explore and analyse the association between biofilm and the genetic polymorphisms of scrA gene of EnzymeIIscr found in clinical isolates of Streptococcus mutans (S. mutans) from severe early childhood caries (S-ECC) in 3 years old children. Methods Clinical strains of S. mutans were conserved from a previous study. Thirty strains of S. mutans from the S-ECC group and 30 strains of S. mutans from the caries free (CF) group were selected. Biomass and viability of biofilm formed by the strains were evaluated by crystal violet and alamar blue assay. Genomic DNA was extracted from the S. mutans isolates. PCR was conducted to amplify scrA gene. After purified and sequenced the PCR products, BioEdit sofeware was used to analyse the sequence results. A chi-square test was used to compare the results. Results Compared to the CF group, the biomass of S-ECC group was higher (P = 0.0424). However, the viability of the two groups showed no significant difference. All 60 clinically isolated S. mutans strains had a 1995 base pair (bp) scrA gene. Forty-nine point mutations were identified in scrA from the 60 clinical isolates. There were 17 missense point mutations at the 10, 65, 103, 284, 289, 925, 1444, 1487, 1494, 1508, 1553, 1576, 1786, 1822, 1863, 1886, and 1925 bp positions. The other 32 mutations were silent point mutations. No positions were found at active sites of ScrA. The statistic analyse showed no significant missense mutation rates between the two groups. Conclusions There was no association between biofilm and genetic polymorphisms of scrA from S. mutans with S-ECC in 3 years old children.